2015
DOI: 10.1371/journal.pone.0144491
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Usage of Reducible Poly(oligo-D-arginine) As a Gene Carrier for Vascular Endothelial Growth Factor Expression

Abstract: Developments of non-viral carriers have headed toward reducing cytotoxicity, which results from the use of conventional gene carriers, and enhancing gene delivery efficiency. Cys-(d-R9)-Cys repeated reducible poly(oligo-D-arginine) (rPOA) is one of the most efficient non-viral carriers for gene therapy; however, while its efficiency has been verified in the lung and brain, it is necessary to confirm its activity in each organ or tissue since there are differences of gene carrier susceptibility to among tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Table 2 presents the main factors evaluated in the articles about to the efficiency of gene transfection and bacterial transformation by different biopolymers and polysaccharides derivates: chitosan [19], dextran [20,21], quaternized cellulose [22] and quaternized chitosan [23]. Other types of substances were used as nonviral vectors such as: plasmid DNA nanostructures with ionic liquid [11], pegylated polyethyleneimine nanoparticles conjugated with folate and galactose [24], cationic liposomes modified with polyallylamine [25], biodegradable polylactic acid-polyethylene glycol-poly (L-lysine) copolymer [26], crotamine [27], poly (oligo-D-arginine) [28], poly (lactic acid-co-glycolic acid) scaffolds [29], polyethyleneimine/pDNA nanocomplexes with anionic hyaluronic acid [30], fourth generation cationic phosphorus (P4) containing dendrimers [31], and monosylated polyethyleneimine [32]. All the materials tested on these studies showed low cytotoxicity and enhanced significantly the efficiency (p < 0.05).…”
Section: Discussion Of Articlesmentioning
confidence: 99%
“…Table 2 presents the main factors evaluated in the articles about to the efficiency of gene transfection and bacterial transformation by different biopolymers and polysaccharides derivates: chitosan [19], dextran [20,21], quaternized cellulose [22] and quaternized chitosan [23]. Other types of substances were used as nonviral vectors such as: plasmid DNA nanostructures with ionic liquid [11], pegylated polyethyleneimine nanoparticles conjugated with folate and galactose [24], cationic liposomes modified with polyallylamine [25], biodegradable polylactic acid-polyethylene glycol-poly (L-lysine) copolymer [26], crotamine [27], poly (oligo-D-arginine) [28], poly (lactic acid-co-glycolic acid) scaffolds [29], polyethyleneimine/pDNA nanocomplexes with anionic hyaluronic acid [30], fourth generation cationic phosphorus (P4) containing dendrimers [31], and monosylated polyethyleneimine [32]. All the materials tested on these studies showed low cytotoxicity and enhanced significantly the efficiency (p < 0.05).…”
Section: Discussion Of Articlesmentioning
confidence: 99%
“…Lesion size measured by computer-associated morphometry revealed a 30% decrease in the mean lesion area of the aortic sinus, for groups treated with peptiplexes, compared to the control groups ( Figure 10 D,E). Several other in vivo studies validated reducible poly(oligo-D-arginine) (rPOA)/pDNA complexes as an efficient non-viral gene carrier in the treatment of hypoxic–ischemic brain injury, spinal cord tumors, and in ischemic heart and lung diseases [ 140 , 141 , 142 , 143 ].…”
Section: In Vivo Applications Of Peptide-based Nanoassemblies For mentioning
confidence: 99%
“…Other groups have also found that poly-arginine peptides are about to inhibit neuronal cell death by reducing stress-induced hyperpolarization of the mitochondria [ 63 , 138 , 139 , 140 , 141 ]. Additionally, poly-D-arginine peptides have been shown to be of use in gene therapy as non-viral carriers of genes [ 142 , 143 , 144 , 145 ]. This is due to their promotion of cell survival, allowing for introduction of a new gene while simultaneously preventing cellular stress [ 142 , 143 , 144 , 145 ].…”
Section: Inactive D-amino Acids With Interesting Derivatives or Otmentioning
confidence: 99%
“…Additionally, poly-D-arginine peptides have been shown to be of use in gene therapy as non-viral carriers of genes [ 142 , 143 , 144 , 145 ]. This is due to their promotion of cell survival, allowing for introduction of a new gene while simultaneously preventing cellular stress [ 142 , 143 , 144 , 145 ]. This shows that D-arginine’s neuroprotective effects make it a useful tool for decreasing infarct volume after stroke, ischemic or hypoxic damage to the brain.…”
Section: Inactive D-amino Acids With Interesting Derivatives or Otmentioning
confidence: 99%